2011
DOI: 10.1111/j.1574-6968.2011.02328.x
|View full text |Cite
|
Sign up to set email alerts
|

Quorum-sensing autoinducer molecules produced by members of a multispecies biofilm promote horizontal gene transfer to Vibrio cholerae

Abstract: Vibrio cholerae, the causative agent of cholera and a natural inhabitant of aquatic environments, regulates numerous behaviors using a quorum-sensing (QS) system conserved among many members of the marine genus Vibrio. The Vibrio QS response is mediated by two extracellular autoinducer (AI) molecules: CAI-I, which is produced only by Vibrios, and AI-2, which is produced by many bacteria. In marine biofilms on chitinous surfaces, QS-proficient V. cholerae become naturally competent to take up extracellular DNA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
104
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 98 publications
(108 citation statements)
references
References 53 publications
1
104
2
1
Order By: Relevance
“…The formation of a biofilm enhances the resistance for outer pressure and may cause many problems in the food industry. Studies have demonstrated that QS may be involved in the process of exoenzyme activities and biofilm formation: protease production in Pseudomonas fluorescens was regulated by AHLs (Liu et al, 2007); the application of furanones (QS inhibitor) prolonged the shelf-life of fermented milk by reducing the motility and exoenzyme activity of Pseudomonas fluorescens (Shobharani and Agrawal, 2010); and QS regulated biofilm formation in Vibrio cholerae (Antonova and Hammer, 2011). Mainly, the role of AHLs-producing bacteria in the process of refrigerated turbot spoilage suggests a possible link between a QS system and spoilage, which necessitates a new strategy for refrigerated turbot preservation.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of a biofilm enhances the resistance for outer pressure and may cause many problems in the food industry. Studies have demonstrated that QS may be involved in the process of exoenzyme activities and biofilm formation: protease production in Pseudomonas fluorescens was regulated by AHLs (Liu et al, 2007); the application of furanones (QS inhibitor) prolonged the shelf-life of fermented milk by reducing the motility and exoenzyme activity of Pseudomonas fluorescens (Shobharani and Agrawal, 2010); and QS regulated biofilm formation in Vibrio cholerae (Antonova and Hammer, 2011). Mainly, the role of AHLs-producing bacteria in the process of refrigerated turbot spoilage suggests a possible link between a QS system and spoilage, which necessitates a new strategy for refrigerated turbot preservation.…”
Section: Introductionmentioning
confidence: 99%
“…However, Gram + QS system utilizes distinct peptide-based QS systems unrelated to the system used by V. cholerae and other Gram − vibrios (99). Nonetheless, the role of QS as a positive regulator in V. cholerae like in other bacteria has been proposed to provide a mechanism to increase the likelihood of taking up extracellular DNA from self or related vibrios (23,100).…”
Section: Grammentioning
confidence: 99%
“…According to the findings, the DNA-uptake complex that depends on a Type IV pilus translocates foreign DNAs across outer membrane while a pilus-independent shuttling system, which is made and controlled by a 19-gene regulon, brings the DNA into cytoplasm. What is notable is that competence of V. cholerae in biofilms formed on chitin materials are also regulated by quorum sensing (Antonova and Hammer, 2011;Lo Scrudato and Blokesch, 2013). In nature, the natural competence will allow V. cholerae to uptake genetic materials from other bacteria that are present in biofilms in marine environments.…”
mentioning
confidence: 99%